How to Use the New Florida Citrus Rootstock Selection Guide - Rhuanito Soranz Ferrarezi; William S. Castle; Kim D. Bowman; Jude W. Grosser; Stephen H. Futch; Steve Rogers; Andres Gonzalez (EDIS, 2020)
First published in 1989 as Rootstocks for Florida Citrus, the work of Dr. William Castle and his colleagues remains relevant 30 years later. The purpose of the Florida Citrus Rootstock Selection Guide (FLCRSG) is to provide timely and useful citrus rootstock information to help Florida citrus growers make well-grounded, practical decisions. New problems with abiotic factors, pests, and diseases make the FLCRSG a standard document for the Florida citrus industry. Initially published as a book, it was integrated into an informative wheel and is now a web-based expert system with an interactive table with 21 characteristics of 48 rootstocks.